Where do gazelles and high-growth firms occur in Germany? - Matthias Tomenendal; Christian Raffer (Berlin School of Economics and Law (HWR Berlin), Berlin Professional School (BPS), 2023)
There is still a rather small number of studies on gazelles in Germany, home to Europe's largest economy and its capital Berlin, one of Europe's main startup hubs. In particular, a recent overview on the occurrence of gazelles in Germany, which differentiates gazelles (up to five years old) from other high-growth firms (no age restriction) is missing. Applying descriptive statistics to a data set of 5,328 high-growth firms we provide such an overview in terms of regional and sectoral distribution of German gazelles as well as their spatial link to regional business clusters. We find that most German high-growth firms (and equally gazelles) exist in the most populated German states. They mostly exist in traditional business sectors like construction and manufacturing. Relatively more gazelles than older high-growth firms exist in the sector of further business-related services. In the sectors construction, information and communication, further business-related services, and art, entertainment and recreation, we identify weak but significant positive spatial associations between the number of cluster initiatives and the number of gazelles. No such association exists for the entirety of high-growth firms in Germany. – – Noch immer gibt es wenige Studien über Gazellenunternehmen in Deutschland, obwohl Deutschland die größte Volkswirtschaft Europas darstellt und die Hauptstadt Berlin ein Zentrum von Unternehmensgründungen ist. Es mangelt insbesondere an aktuellen Studien, die Gazellen im engeren Sinne (bis zu fünf Jahre alt) von schnell wachsenden Unternehmen (keine Altersbeschränkung) unterscheiden. Unsere Studie von 5.328 schnell wachsenden Unternehmen in Deutschland verschafft einen aktuellen und differenzierten Überblick über die sektorale und regionale Verteilung dieser Firmen wie auch ihre Nähe zu offiziellen Clustern. Im Ergebnis finden sich die meisten Gazellen und schnell wachsenden Unternehmen in den bevölkerungsreichsten Bundesländern, vorwiegend in traditionellen Sektoren wie dem Bau- und dem verarbeitenden Gewerbe. Gazellen gibt es vergleichsweise häufiger im Sektor der weiteren Dienstleistungen. Eine signifikante, wenn auch schwache Korrelation zwischen den Standorten von Gazellen und Clustern ergibt sich für die Sektoren Baugewerbe, Informations- und Kommunikationswirtschaft, weitere Dienstleistungen sowie Kunst, Unterhaltung und Erholung.
Keywords: 330; gazelles; German gazelles; high-growth firms; distribution of gazelles; occurrence of gazelles; clusters; cluster embeddedness; Unternehmensgründung; Unternehmenswachstum; Räumliche Verteilung; Statistik; Deutschland